Diretrizes para o relato preciso e transparente de estimativas de saúde: a Declaração GATHER - Stevens, G; Alkema, L; Black, R; Boerma, J; Collins, G; Ezzati, M; Grove, J; Hogan, D; Hogan, M; Horton, R; Lawn, J; Marušic, A; et al. (Ministério da Saúde do Brasil, 2017)
Measurements of health indicators are rarely available for every population and period of interest, and available data may not be comparable. The Guidelines for Accurate and Transparent Health Estimates Reporting (GATHER) define best reporting practices for studies that calculate health estimates for multiple populations (in time or space) using multiple information sources. Health estimates that fall within the scope of GATHER include all quantitative population-level estimates (including global, regional, national, or subnational estimates) of health indicators, including indicators of health status, incidence and prevalence of diseases, injuries, and disability and functioning; and indicators of health determinants, including health behaviours and health exposures. GATHER comprises a checklist of 18 items that are essential for best reporting practice. A more detailed explanation and elaboration document, describing the interpretation and rationale of each reporting item along with examples of good reporting, is available on the GATHER website (http://gather-statement.org).